The local politics of rural land use: Place, extraction industries and narratives of contemporary rurality. (June 2019) - Farrugia, David; Hanley, Joanne; Sherval, Meg; Askland, Hedda; Askew, Michael; Coffey, Julia; Threadgold, Steven
This article contributes to discussions of place and social change in rural sociology with a focus on the local politics of rural land use. In particular, the article explores the way that one rural place is responding to changes in the local and regional economy connected with the arrival of extractive industries such as mining and coal seam gas (CSG). The article shows how attitudes towards extractive industries are formed through notions of place and community within broader narratives concerning rurality and global capitalism. The local politics of land use enrols complex and contradictory forms of place attachment into the articulation of competing narratives about rurality, and intervenes in the local social relationships of rural areas. The politics of extraction in rural Australia is therefore situated at the forefront of contemporary economic and cultural changes that are part of the reshaping of place amid the broader dynamics of contemporary global capitalism.